Freudian analysts/feminist issues - Hughes, Judith M. (Yale University Press, 1999)
In this book Judith M. Hughes makes a highly original case for conceptualizing gender identity as potentially multiple. She does so by situating her argument within the history of psychoanalysis. Hughes traces a series of conceptual lineages, each descending from Freud. In the study Helene Deutsch, Karen Horney, and Melanie Klein occupy prominent places. So too do Erik H. Erikson and Robert J. Stoller. Among contemporary theorists Carol Gilligan and Nancy Chodorow are included in Hughes's roster. In each lineage Hughes discerns an evolutionary narrative: Deutsch tells a story of retrogression; Erikson names his epigenesis, and Gilligan continues in that vein; Horney's discussion recalls sexual selection; Stoller's and Chodorow's theorizing brings artificial selection to mind; and finally in Klein's work Hughes sees a story of natural selection and adds to it her own notion of multiple gender identities.